Hospital nursing, care quality, and patient satisfaction: Cross-sectional surveys of nurses and patients in hospitals in China and Europe - You, Li-ming; Aiken, Linda H.; Sloane, Douglas M.; Liu, Ke; He, Guo-ping; Hu, Yan; Jiang, Xiao-lian; Li, Xiao-han; Li, Xiao-mei; Liu, Hua-ping; Shang, Shao-mei; Kutney-Lee, Ann; et al. (International journal of nursing studies, 2013)
This study provides a comprehensive evaluation of nurse resources in Chinese hospitals and the link between nurse resources and nurse and patient outcomes. Survey data were used from 9688 nurses and 5786 patients in 181 Chinese hospitals to estimate associations between nurse workforce characteristics and nurse and patient outcomes in China. Nurse and patient assessments in China were compared with a similar study in Europe. Thirty-eight percent of nurses in China had high burnout and 45% were dissatisfied with their jobs. Substantial percentages of nurses described their work environment and the quality of care on their unit as poor or fair (61% and 29%, respectively) and graded their hospital low on patient safety (36%). These outcomes tend to be somewhat poorer in China than in Europe, though fewer nurses in China gave their hospitals poor safety grades. Nurses in Chinese hospitals with better work environments and higher nurse-assessed safety grades had lower odds of high burnout and job dissatisfaction (ORs ranged from 0.56 to 0.75) and of reporting poor or fair quality patient care (ORs ranged from 0.54 to 0.74), and patients in such hospitals were more likely to rate their hospital highly, to be satisfied with nursing communications, and to recommend their hospitals (significant ORs ranged from 1.24 to 1.40). Higher patient-to-nurse ratios were associated with poorer nurse outcomes (each additional patient per nurse increases both burnout and dissatisfaction by a factor of 1.04) and higher likelihoods of nurses reporting poor or fair quality of care (OR=1.05), but were unrelated to patient outcomes. Higher percentages of baccalaureate nurses were strongly related to better patient outcomes, with each 10% increase in the percent of baccalaureate nurses increasing patient satisfaction, high ratings, and willingness to recommend their hospital by factors ranging from 1.11 to 1.13. Nursing is important in quality and safety of hospital care and in patients’ perceptions of their care. Improving quality of hospital work environments and expanding the number of baccalaureate-prepared nurses hold promise for improving hospital outcomes in China.